Community involvement in the identification of vulnerable child-headed households in Hogsback, Eastern Cape Province, South Africa - Mabemba , Tafadzwa; Tanga, Pius T. (Social Work/Maatskaplike Werk, 2025)
Children from child-headed households are vulnerable, as they experience several challenges; it is therefore imperative to provide them with social support. However, the lingering problem in this endeavour is that it is rather difficult to identify such households. To overcome this difficulty, the community should be involved in the identification of these households. This qualitative study sought to describe the community members’ involvement in the identification of vulnerable child-headed households in Hogsback, Eastern Cape province, South Africa. The data were collected through a discussion with one focus group, consisting of ten community members from the Hogsback area. In addition, five social workers from the Department of Social Development in Alice were interviewed individually. The triangulation of the two data sets ensured credibility. Thematic analysis was employed to interpret the data. Two main themes emerged from the discussions. Firstly, community members are aware of, and capable of making observations and reports on children in need. Secondly, community leaders play a key role in identifying vulnerable children. Thus, enhanced community involvement can help social workers to identify vulnerable children from child-headed families with ease. The study recommended educating communities on reporting, identification, and early-intervention procedures to ensure timely and effective responses.